Upaya Peningkatan Aktivitas Fisik Keluarga Tn.K Dengan Diabetes Melitus Di Begajah Sukoharjo - YUNINDRA, CHARIN; , H.M. Abi Muhlisin, SKM.,M.Kep (2016)
Diabetes mellitus is a chronic disease, characterized by progressive inability of the body to metabolize carbohydrates, fats, and potein onset hyperglikemia . Physical Activity will increase the sense of comfort, both physically, psychologically and socially, and looked healthy. For patients with diabetes mellitus, physical activity can reduce the risk of cardiovascular events as well as life expectancy increases. Diabetetes international federation in 2012 mentioned that there are currently about 371 million diabetic patients, in Asia the number of patients with diabetes there are 70 million people 7.6 million are in Indonesia. Deaths due to diabetes in 2012 4.8 million people Pravelensi insulin-dependent diabetes in profinsi Central Java in 2012 amounted to 12:06 is lower than in 2011 (12:09%). Pravelensi highest Semarang regency of 0.66%. while pravelensi cases of insulin-dependent diabetes mellitus known as Type II diabetes, decreased from 0.63% to 0:55 Pravalensi% in 2012. The highest was at 7.93% Magelang. The author uses the description method, the sample with the patient K, in obtaining the data by : interviews, observation, physical examination, and documentation of journals and books. After the interventionn and implementation of nursing a family for one week of diagnosis that appear are: physical weakness, nutrition and the risk of diabetic wounds. In the implementation of nursing authors mostly to use health education in accordance with the action plan that has been done and teach passive ROM, exercises performed by patient who are accompanied by health workers who have been able to be done by the patient with cooperative. Cooperation between the teams of health workers and family are necessary to achieve success in accordance with the action plan family nursing. So that problems in patients with physical weakness, can be resolved.